Determinants of share price movement on Government-Linked Companies in Malaysia / Mazurina Mohd Ali … [et al.] - Mohd Yussof, Mohd Naim; Hasnan, Suhaily; Md Daud, Seri Ayu Masuri (Faculty of Accountancy, 2019)
Government linked companies (GLCs) play a vital role in the growth of the economy in Malaysia. Nonetheless, the perception from the public at large towards GLCs in Malaysia has been tainted by the bad performance of GLCs such as Malaysia Airline System Berhad and Proton Holdings Berhad. Using 17 GLCs listed on the Bursa Malaysia, this study aims to examine the determinants of share prices for the GLCs in Malaysia over the period from 2013 to 2017. A linear multiple regression analysis was used to determine whether or not the independent variables, namely return on asset, return on equity, dividend per share, price earnings ratio, current ratio and acid test ratio influence the share prices. The result of this study shows that those variables accounts for 69.6% of GLCs share price movements. Additionally, dividend per share, price earnings ratio and acid test ratio are significantly positively related to share prices. These findings imply that in order for managers to create value for their shareholders, they should increase the dividend paid to shareholders, increase company’s earnings and have more liquid assets.